ANALISIS KORELASI KINERJA KEUANGAN PERUSAHAAN DENGAN HARGA SAHAM ( STUDI KASUS BANK MANDIRI Tbk ) - Meiffa Herfianti (Unib Press Universitas Bengkulu, 2017)
The purpose of this research is to determine the correlation between the internal performance with the stock prices of Bank Mandiri Tbk. During the period of the year 1999 up to the year of 2008. Those internal performance are Net income, Return On Assets, Return On Equity, Net Profit Margin, and Total Assets. The stock prices of Bank Mandiri Tbk. is the closing prices each the end of year1999 up to year of 2008. The data of this research are selected from the Jakarta Stock Exchange Waeth wich is published in the year of 2008/2009. The analysis was based on the bi- variate correlation analysis of SPSS. The result shows only the performance of Return On Assets (ROA) and Net Income (NI) that having strong positive correlation with the stock prices of Bank Mandiri Tbk. The performance indicators such as Return On Equity (ROE), NetProfit Margin (NPM), and Total Assets (TA) in case of Bank Mandiri Tbk. is not relevance with the stock prices movement.